131 Difficulties faced by early career researchers engaged in overdiagnosis research and solutions for overcoming them. (8th June 2022) - Johansson, Minna; Kalager, Mette; Agarwal, Arnav; Copp, Tessa
Abstract : Overdiagnosis is a counterintuitive topic that challenges aspects of conventional medicine, the intuitive belief in early detection, and society's deep faith in medical technology. It goes against cultural norms such as 'more is better', 'knowledge is power' and 'experts know best'. Researchers involved in this space may therefore encounter obstacles to conducting scholarly work and challenges to communicating their findings. These difficulties may also carry personal costs and impediments to professional progress. While not unique to this field of research, resistance to conducting and disseminating overdiagnosis research is frequent and may be severe. This session will make use of first-hand experiences of researchers working in this area, and, through discussion, propose practical solutions to mitigate and safeguard against adverse consequences when conducting overdiagnosis research. The format of this workshop will involve short presentations on and discussion of: Sharing personal experiences; Potential solutions to challenges encountered, and steps to: minimize the risk of adverse academic, personal and professional costs; and maintain engagement in academic discussion and evidence based health care. Learning Objectives: By the end of the session, participants will have - Increased awareness of academic, personal and professional difficulties and costs encountered when undertaking research on overdiagnosis; and be able to – Identify drivers of resistance to overdiagnosis research; Outline possible solutions to challenges encountered at individual and system levels; and Form support systems